Edukacja akademicka kobiet w przekazie prasy społeczno-kulturalnej i pedagogicznej Królestwa Polskiego na przełomie XIX i XX wieku - Krakowiak, Małgorzata (Biuletyn Historii Wychowania, 2020)
The purpose of the article is to present a journalistic description of the issue of academic education of women in selected periodicals of the Kingdom of Poland in the years 1894–1914. The issue of women’s academic education was described in various ways, which depended on the profile of individual periodicals. The publications had mainly an opinion-forming and informative function. Critical opinions were published in the conservative press, they showed study abroad as a danger. Progressive magazines described women’s studies as a chance for girls development. Periodicals were a source of information about the number of women undertaking academic education abroad, selected faculties and student societies. The frequency of publications depended on legislative changes and events related to academic life that aroused public and public interest. This article looked for answers to the question of how the issue of academic education of women from the Kingdom of Poland was problematized in selected press? In the article uses the methods of historical and pedagogical research and press research (text analysis). Research on the journalistic description of women’s academic education should be continued based on other categories of periodicals, including women’s press.